2016
DOI: 10.1182/blood.v128.22.3628.3628
|View full text |Cite
|
Sign up to set email alerts
|

Children with Thalassemia Major Display Abnormal Renal Tubular Function

Abstract: Introduction. Chronic hypoxia, transfusional iron overload and chelation therapy are all contributing factors to the deterioration of renal function in thalassemia major (TM ) patients. Among chelators, deferasirox (DFX) is considered the most toxic drug for kidneys: increment of more than 30% of serum creatinine levels is used for dosage modulation or interruption. Recently tubular abnormalities have also been described. We have observed renal toxicity in nine children affected by TM and treated with DFX or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Numerous studies have corroborated these findings, supporting the observed results [24][25][26]. The serum creatinine test is commonly employed to assess glomerular function [27]. Our study observed a significant decrease (P ≤ 0.05) in patients' creatinine levels.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have corroborated these findings, supporting the observed results [24][25][26]. The serum creatinine test is commonly employed to assess glomerular function [27]. Our study observed a significant decrease (P ≤ 0.05) in patients' creatinine levels.…”
Section: Discussionsupporting
confidence: 89%